Development of an empirical model to predict the burst pressure of corroded elbows of pipelines by finite element modelling. (February 2022) - Shuai, Yi; Zhang, Xiao; Huang, Hui; Feng, Can; Cheng, Y. Frank
Abstract: Burst capacity assessment at a corrosion defect of pipe elbows subjected to internal pressure is essential for oil/gas pipeline integrity management. In this study, a three-dimensional (3D) nonlinear finite element (FE) model validated by burst tests was developed to investigate the effect of corrosion defects on the burst capacity of X80 pipe elbows. Subsequently, the effects of corrosion geometry (i.e. depth, length, and width of the defect) on the pipe burst pressure were determined. Based on the Goodall model of intact pipe elbows, a reasonable mathematical expression for the failure pressure prediction formula for corroded pipelines under external loads was derived by introducing a defect geometry factor function. Then, combined with a series of FE cases, a new prediction model of burst pressure for corroded pipe elbows experiencing internal pressure was developed. Finally, the accuracy and reliability of the proposed model were verified using extensive parametric FE analysis. The results show that the average error of failure pressure between the proposed model and FEM was only 3.63% for 291 cases. Moreover, the prediction accuracy was better than other well-known models. Therefore, the proposed model can be widely used in the safety assessment of corroded elbows of oil/gas pipelines. Highlights: A novel model for predicting the ultimate burst capacity of corroded pipe elbows. A finite element model for burst analysis on corroded elbows. Determined the failure pressure of pipe elbows containing a corrosion defect. Dependence of the burst capacity of elbows on corrosion defect geometry.